Adherence to best practice consensus guidelines for implant-based breast reconstruction: Results from the iBRA national practice questionnaire survey - Mylvaganam, S; Conroy, E; Williamson, P; Barnes, N; Cutress, R; Gardiner, M; Jain, A; Skillman, J; Thrush, S; Whisker, L; Blazeby, J; Potter, S; et al. (Elsevier, 2018)
Introductions The 2008 National Mastectomy and Breast Reconstruction Audit demonstrated marked variation in the practice and outcomes of breast reconstruction in the UK. To standardise practice and improve outcomes for patients, the British professional associations developed best-practice guidelines with specific guidance for newer mesh-assisted implant-based techniques. We explored the degree of uptake of best-practice guidelines within units performing implant-based reconstruction (IBBR) as the first phase of the implant Breast Reconstruction Evaluation (iBRA) study. Methods A questionnaire developed by the iBRA Steering Group was completed by trainee and consultant leads at breast and plastic surgical units across the UK. Simple summary statistics were calculated for each survey item to assess compliance with current best-practice guidelines. Results 81 units from 79 NHS Trusts completed the questionnaire. Marked variation was observed in adherence to guidelines, especially those relating to clinical governance and infection prevention strategies. Less than half (n = 28, 47%) of units obtained local clinical governance board approval prior to offering new mesh-based techniques and prospective audit of the clinical, cosmetic and patient-reported outcomes of surgery was infrequent. Most units screened for methicillin-resistant staphylococcus aureus prior to surgery but fewer than 1 in 3 screened for methicillin-sensitive strains. Laminar-flow theatres (recommended for IBBR) were not widely-available with less than 1 in 5 units having regular access. Perioperative antibiotics were widely-used, but the type and duration were highly-variable.